Investigation of the Calcium Signaling in Subpopulation of Rat Sensory Neurones: Relationships Between Capsaicin Sensitivity, Nonspecific Depolarisation and Cell Size - Ozcan, Mete; Alcin, Erguel; Kuzgun, Kemal Tugrul; Kelestimur, Haluk; Ayar, Ahmet (Ortadogu Ad Pres & Publ Co, 2010)
Objective: The concentration of free intracellular Ca2+ ([Ca2+](i)) influences neuronal properties including regulation of excitability and neurotransmitter release. The aim of this study was to investigate relationships between capsaicin sensitivity and cell size in acutely isolated dorsal root ganglion (DRG) neurons, in order to ascertain whether a particular diameter range is involved in nociception. Material and Methods: Following decapitation, dorsal root ganglia were excised, enzymatically treated and plated on coated coverslips following mechanical isolation, and cultured in a tissue culture containing nerve growth factor for a short time. Based on the size of cell trunk, DRG neurons were divided into three categories: small, medium and large. Responses to capsaicin (1 mu M) and depolarization by high KCl+ (30 mM) were studied by monitoring changes in [Ca2+](i) with a microscopic digital image analysis system in fura-2 loaded single neurons. Results: There were marked differences between subpopulations of neurons with respect to Ca2+ responses to the KCl and capsaicin, with the largest [Ca2+](i) transients in small-diameter neurons to capsaicin while all subtypes gave similar responses to KCl. Conclusion: These results suggest that different sized DRG neurons are also heterogeneous functionally. Significantly more capsaicin-sensitivity of small-diameter DRG neurons indicates that these nociceptors may serve potential nociceptive cellular model for the development of novel analgesics.
Sıçan duyusal sinir hücresi alt tiplerinde kalsiyum sinyallerinin i?ncelenmesi: Kapsaisin duyarlılı?ı, nonspesifik depolarizasyon ve hücre çapı arasındaki i?lişki;
Keywords: Capsaicin; pain measurement; calcium